2016
DOI: 10.1371/journal.pntd.0004601
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica Surface Coat Glycoproteins Contain Mannosylated and Phosphorylated N-glycans and Exhibit Immune Modulatory Properties Independent of the Mannose Receptor

Abstract: Fascioliasis, caused by the liver fluke Fasciola hepatica, is a neglected tropical disease infecting over 1 million individuals annually with 17 million people at risk of infection. Like other helminths, F. hepatica employs mechanisms of immune suppression in order to evade its host immune system. In this study the N-glycosylation of F. hepatica’s tegumental coat (FhTeg) and its carbohydrate-dependent interactions with bone marrow derived dendritic cells (BMDCs) were investigated. Mass spectrometric analysis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 74 publications
1
51
0
Order By: Relevance
“…The importance of these carbohydrate residues is re-enforced by the finding that tegumental antigens (Teg) induce angeric T-cells via dendritic cells (DCs) in a mannose receptor (MR)-dependent fashion . A second study from the same group, however, demonstrated that despite the role of the mannose receptor binding components in Teg not all of its effects were MR-dependent (Ravid a et al, 2016).…”
Section: Parasite Recognition and Innate Effectorsmentioning
confidence: 97%
See 1 more Smart Citation
“…The importance of these carbohydrate residues is re-enforced by the finding that tegumental antigens (Teg) induce angeric T-cells via dendritic cells (DCs) in a mannose receptor (MR)-dependent fashion . A second study from the same group, however, demonstrated that despite the role of the mannose receptor binding components in Teg not all of its effects were MR-dependent (Ravid a et al, 2016).…”
Section: Parasite Recognition and Innate Effectorsmentioning
confidence: 97%
“…The importance of these carbohydrate residues is re‐enforced by the finding that tegumental antigens (Teg) induce angeric T‐cells via dendritic cells (DCs) in a mannose receptor (MR)‐dependent fashion (Aldridge & O'Neill, ). A second study from the same group, however, demonstrated that despite the role of the mannose receptor binding components in Teg not all of its effects were MR‐dependent (Ravidà et al., ). Indeed the effects of Teg on DCs are known to TLR4‐independent (Hamilton et al., ), while those of excretory/secretory (ES) antigen on the same cell type is partially TLR4‐dependent (Dowling et al., ).…”
Section: Immunity To Fasciola Sppmentioning
confidence: 99%
“…To date F. hepatica glycomic analyses have focussed on the outer surface of the parasite, the glycocalyx, that is rich in glycoproteins and glycolipids (Threadgold, 1976). Analysis has shown that the tegumental surface is highly glycosylated, with an abundance of mannose-rich N-linked glycoproteins present on the surface, spines and suckers (Garcia-Campos et al, 2016;Ravida et al, 2016a;Ravida et al, 2016b). The exact role these N-glycoproteins play at the host-parasite interface is currently unknown, though parasite glyco-conjugates that been implicated in evading the host immune response (van Die and Cummings, 2010).…”
Section: Glycomicsmentioning
confidence: 99%
“…Very recent reports3334, including our own32, have brought insights about the role of F. hepatica glycans in mediating the regulation of DC-maturation through CLR recognition. Our group has recently described that glycan structures produced by F. hepatica participate in the modulation of bone marrow-derived DCs (BMDCs) and induce/mediate the production of IL-10 and IL-4 during infection32.…”
mentioning
confidence: 96%